HAEMOGLOBIN AND PLASMA BIOCHEMICAL PROFILE OF REPEAT BREEDER CATTLE ON THE DAY OF ESTRUS COULD PLAY A ROLE IN EXHIBITION OF ESTRUS AND SUBSEQUENT PREGNANCY OUTCOME - KUNDE, A A S; RAJU, M S; MURUGAVEL, K; THANISLASS, J (The Indian Journal of Animal Reproduction, 2022)
On the day of induced estrus, jugular vein blood samples were collected from healthy repeat breeder cattle(n=45) for the estimation of haemoglobin, glucose, cholesterol and total protein, followed by pregnancy diagnosison day 45 post-insemination. There was no difference (p
Keywords: Biochemical constituents; Cattle; Estrus; Haemoglobin; Pregnancy